For peace, justice, and the integrity of creation: The Conciliar Process and the transformation of religious engagement in the Netherlands, 1987-1992 - Dam, Peter van (Trajecta, 2024)
The Conciliar Process was a transnational campaign initiated by churches throughout the world, adhorting Christians to consider their responsibility for global justice, peace, and the environment. This article analyses the trajectory of this campaign, also known as the campaign for Justice, Peace and the integrity of Creation (JPIC), as it unfolded between 1987 and 1992. If focuses primarily on its evolution in the Netherlands, where it was received enthusiastically. With the Conciliar Process, a mode of religiously inspired civic initiative which favored an integration of spiritual and worldly domains, a broad range of issues, and an expansive range of civic organizations culminated. The trajectory of the campaign highlights a transformation of civic engagement by church members, who shifted their activities towards local initiatives and professional nongovernmental organizations. These shifts resulted from three coinciding dimensions: the structural developments of fluidization and professionalization, the end of the Cold War, and the drive to overcome internal divisions and engage in lowthreshold activities. This history thus provides a new framework to grasp the trajectories of persistence and transformation in religious life in Europe since the 1990s.